1995
DOI: 10.1007/bf00311830
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous rupture of the iliac vein: Report of a case

Abstract: We report a rare case of a spontaneous rupture of the iliac vein which was then surgically treated with good results. A 66-year-old woman was admitted complaining of leg swelling and lower abdominal pain. On the 3rd day after admission, an operation was performed because of a gradually increasing hematoma in the retroperitoneal space. Laparotomy revealed a 17 mm longitudinal tear on the anterior surface of the left external iliac vein with a thrombus inside the lumen. Most of the previously reported 14 cases o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 9 publications
0
14
0
1
Order By: Relevance
“…2 However, hematomas of the lateral abdominal wall caused by a rupture of the deep circumflex iliac artery, including both spontaneous and traumatic cases, are very rare. [3][4][5] Katsumori et al reported a spontaneous hemorrhage from a deep circumflex iliac artery, 6 and Lefere et al reported an expanding hematoma of the lateral abdominal wall after blunt abdominal trauma. 7 Irifune et al also reported an abdominal wall hematoma in an adolescent javelin thrower.…”
Section: Discussionmentioning
confidence: 98%
“…2 However, hematomas of the lateral abdominal wall caused by a rupture of the deep circumflex iliac artery, including both spontaneous and traumatic cases, are very rare. [3][4][5] Katsumori et al reported a spontaneous hemorrhage from a deep circumflex iliac artery, 6 and Lefere et al reported an expanding hematoma of the lateral abdominal wall after blunt abdominal trauma. 7 Irifune et al also reported an abdominal wall hematoma in an adolescent javelin thrower.…”
Section: Discussionmentioning
confidence: 98%
“…The cause of this condition is not yet known in spite of several proposed etiologies including venous hypertension and constipation [1-6]. We assume that the cause of this case was the result of abdominal pressure rise owing to obesity and sudden position change.…”
Section: Discussionmentioning
confidence: 96%
“…21,22 The mechanism of iliac vein rupture may be a sudden rise in venous pressure in weakened vein due to loss of estrogen, complications of pregnancy, and May-Thurner syndrome. 7 Accurate preoperative diagnosis of SRH was usually difficult. Hypovolemic shock often occurred at presentation, and extensive tests were impossible.…”
Section: Discussionmentioning
confidence: 99%
“…To date, 35 patients with spontaneous iliac vein rupture have been reported, [2][3][4] of which almost 79% had concomitant deep venous thrombosis (DVT) or thrombophlebitis 2 and approximately 28.6% had May-Thurner syndrome. 3,[5][6][7][8][9][10][11][12][13] In this study, we investigated SRH associated with iliac vein rupture. Owing to the inability to institute anticoagulation and initial uncertainty in diagnosis, management of these patients presents significant challenges.…”
mentioning
confidence: 99%